Low-temperature hydrodeoxygenation catalyst as well as preparation method and application thereof

By using phosphorus-modified alumina support and nickel-like hydrodeoxygenation catalysts in Fischer-Tropsch synthetic oil, the problem of difficult to achieve high deoxygenation rate at low temperatures is solved, and efficient low-temperature removal of alcohols is achieved, reducing energy consumption and cost.

CN119897082AActive Publication Date: 2025-04-29PETROCHINA CO LTD

Patent Information

Application Number
CN202311402391.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high deoxygenation rate at low temperatures, especially in Fischer-Tropsch synthetic oil, the low-temperature removal effect of alcohols is poor, and the catalyst has many types of elements, complex manufacturing steps, and high cost.

Method used

Phosphorus-modified alumina support, nickel as the hydrogenation active component, lanthanum, cerium, cobalt and/or zinc as the cocatalyst components, and the components are supported by step-by-step impregnation method to simplify the production process of the catalyst.

Benefits of technology

At low temperatures (190°C to 240°C), the oxygen-containing compounds, especially alcohols in Fischer Tropsch synthetic oil, have been fully removed, and the deoxygenation rate of more than 99%, reducing energy consumption and CO2 emissions, and reducing the element types and manufacturing steps of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004517130040000141
    Figure BDA0004517130040000141
  • Figure BDA0004517130040000151
    Figure BDA0004517130040000151
  • Figure BDA0004517130040000161
    Figure BDA0004517130040000161
Patent Text Reader

Abstract

The invention relates to a low-temperature hydrodeoxygenation catalyst as well as a preparation method and application thereof. The catalyst provided by the invention is suitable for low-temperature removal of alcohols in Fischer-Tropsch synthetic oil, and is also suitable for low-temperature removal of alcohols in other hydrocarbons containing alcohols. The catalyst provided by the invention adopts a phosphorus modified alumina carrier, adopts nickel as a hydrogenation active component, and adopts lanthanum, cerium, cobalt and / or zinc (especially cerium) as a cocatalyst component, and a component loading process adopts a step-by-step impregnation method to load the cocatalyst component and the hydrogenation active component on the carrier in sequence. The catalyst provided by the invention solves the technical problem of sufficient removal of oxygen-containing compounds at low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a low-temperature hydrodeoxygenation catalyst, which is suitable for the low-temperature hydrodeoxygenation refining process of oxygen-containing compounds in Fischer-Tropsch synthetic oil, particularly suitable for the low-temperature removal of alcohols in Fischer-Tropsch synthetic oil, and also suitable for the low-temperature removal of alcohols in other hydrocarbons containing alcohols. In addition, the present invention also relates to a method for preparing the catalyst. Background Art

[0002] With the increasing demand for petroleum-based liquid fuels and the decreasing petroleum resources, Fischer-Tropsch synthetic oil, which is synthesized based on the Fischer-Tropsch synthesis reaction with synthesis gas as raw material, has attracted attention. Fischer-Tropsch synthetic oil contains a high content of olefins and a certain amount of oxygen-containing compounds, such as alcohols, acids, aldehydes, ketones and esters. Even if these oxygen-containing compounds exist in trace amounts, they will have many adverse effects on subsequent processes, such as corrosion of equipment, poisoning and deactivation of olefin polymerization catalysts (the presence of more than 1% of oxygen-containing compounds may cause poisoning and deactivation of olefin polymerization catalysts), etc. Therefore, it is very necessary to fully remove the oxygen-containing compounds in Fischer-Tropsch synthetic oil.

[0003] The crude products of low-temperature Fischer-Tropsch synthesis reaction are mainly light oil, heavy oil and heavy wax. The synthetic oil of different fractions enters the hydrotreating unit to undergo olefin saturation and oxygen-containing compound removal reactions. It can be used to produce environmentally friendly solvent oil, surfactants, high-grade white oil, drilling fluid base oil, etc. It is an effective supplement to petrochemical industry and produces special high-end products that are difficult to produce with petroleum-based raw materials. Hydrodeoxygenation is one of the main methods for removing oxygen-containing compounds in Fischer-Tropsch synthetic oil.

[0004] The active phase of traditional petroleum product hydrorefining catalysts is generally metal sulfide, and the active metal is mainly non-precious metal Ni-Mo, Co-Mo and other systems. Sulfide catalysts need to be pre-sulfurized with sulfur-containing compounds before use. Since Fischer-Tropsch synthetic oil is basically sulfur-free, the sulfur on the catalyst will gradually disappear and become metallic during the reaction and become inactive. Therefore, in order to maintain the activity of the catalyst, the reaction system needs to be regularly filled with sulfurizing agents, but this will cause sulfur elements to appear in the processed products, polluting the Fischer-Tropsch synthetic oil. Metal reduced catalysts do not need to add sulfurizing agents, which not only reduces the process operation of sulfur injection, but also solves the problem of product pollution.

[0005] Patent document 1 discloses a Fischer-Tropsch synthetic oil hydrodeoxygenation catalyst, which is composed of one or more main catalytic active metal components selected from Mo, W, Ni and a carrier, wherein the catalyst can also optionally add any combination of one or more selected from B, P, Co and La as a co-catalytic active component, wherein the carrier is selected from one of an acid-modified alumina carrier, a composite carrier containing molecular sieves and alumina, and a solid acid carrier, or a combination of any two or more thereof. The modified alumina carrier uses a molded alumina carrier impregnated with an acid solution of a certain molar concentration (phosphoric acid, oxalic acid, silicotungstic heteropoly acid or any combination of two or more thereof). In Example 2 of Patent Document 1, the reaction temperature is 245°C and the deoxidation rate is 98.5%.

[0006] However, the inventors have found that the catalyst reaction temperature of Patent Document 1 is high (over 240°C) and the deoxygenation rate can be improved, especially at low temperatures (below 240°C) the deoxygenation rate (i.e., oxygen-containing compound removal rate) is not high enough.

[0007] Patent document 2 discloses a Fischer-Tropsch synthesis oil hydrogenation catalyst, which is mainly composed of hydrogenation active components of nickel oxide and tungsten oxide or molybdenum oxide and a carrier, wherein the co-catalyst is one or a combination of rare earth metal elements lanthanum and cerium, and there is or is not one or any combination of non-metallic elements fluorine, phosphorus and boron. Patent document 2 evaluates the temperature (reaction temperature) of the phosphorus-containing catalyst to be 260°C, and the deoxidation rate is >99%.

[0008] The inventors have found that, in order to achieve a deoxygenation rate of more than 99%, the catalyst of Patent Document 2 requires more types of elements and is more complex (there are two hydrogenation active components). In addition, the reaction temperature of the catalyst of Patent Document 2 is higher and the space velocity is lower. If the catalyst of Patent Document 2 is used at low temperatures, the deoxygenation rate is not high enough.

[0009] Patent document 3 discloses a catalyst for hydrorefining of Fischer-Tropsch synthetic oil, wherein the catalyst is mainly composed of hydrogenation active components nickel oxide, tungsten oxide and aluminum oxide as carriers, wherein one or more of titanium oxide, silicon oxide, zirconium oxide, fluorine, boron and phosphorus are used as additives to modify the carrier. The molded γ-Al2O3 carrier is impregnated with an equal volume of an aqueous solution or organic solution of one or more of the additive components of titanium, silicon, zirconium, fluorine, boron and phosphorus. The evaluation temperature (reaction temperature) of the phosphorus-containing catalyst in Patent Document 3 is 300°C, and the deoxidation rate is 99.76%.

[0010] The present inventors have found that the reaction temperature required for the catalyst of Patent Document 3 to achieve a high deoxygenation rate is as high as 300° C. If the catalyst of Patent Document 3 is used at a low temperature, the deoxygenation rate is not high enough.

[0011] Prior art literature

[0012] Patent document 1: CN102794181B

[0013] Patent document 2: CN101733119B

[0014] Patent document 3: CN103191754A

[0015] Technical Problems to be Solved by the Invention

[0016] It is obviously more economical to achieve a high deoxygenation rate at a relatively low reaction temperature, especially in terms of reducing energy consumption and CO2 emissions.

[0017] The inventors have found that for Fischer-Tropsch synthetic oil, the hydrodeoxygenation reaction is a temperature-sensitive reaction. The deoxygenation rate increases with the increase of reaction temperature. On the contrary, the lower the reaction temperature, the more unfavorable it is for the improvement of the deoxygenation rate. In the actual reaction process, within a certain temperature range, the temperature difference of 10°C will result in a difference of several percentage points in the deoxygenation rate, or even a difference of more than ten or twenty percentage points.

[0018] The catalysts in Patent Documents 1 to 3 can only be used at reaction temperatures exceeding 240°C. The inventors have found that once used at lower temperatures (below 240°C), the deoxidation rates are reduced to varying degrees, which is unsatisfactory.

[0019] In addition, the fewer elements used in the catalyst, the fewer manufacturing steps and the lower the cost. However, according to the examples of Patent Documents 1 to 3, the catalysts of Patent Documents 1 to 3 actually use more elements and have more manufacturing steps.

[0020] Furthermore, Patent Documents 1 to 3 do not pay special attention to the removal of alcohols which account for a large proportion of the Fischer-Tropsch synthetic oil.

[0021] In view of the above defects in the prior art, the object of the present invention is to provide a hydrodeoxygenation catalyst for Fischer-Tropsch oil, which can fully remove oxygen-containing compounds, especially alcohols, at a lower reaction temperature, and the catalyst uses fewer types of elements and has fewer manufacturing steps.

[0022] Solutions to technical problems

[0023] After in-depth research, the inventors found that solving the above technical problems is a complex process, which is related to the selection of hydrogenation active components and co-catalyst components, the properties of the carrier and the preparation method / process of the catalyst. The four factors of hydrogenation active components, co-catalyst components, the properties of the carrier and the preparation method / process of the catalyst are interrelated.

[0024] Based on this discovery, the inventors have conducted extensive research and experiments over a long period of time and finally found that the above technical problems can only be effectively solved when the hydrodeoxygenation catalyst meets the following four main characteristics at the same time.

[0025] Feature 1: Using phosphorus-modified alumina carrier;

[0026] Feature 2: Nickel is used as the hydrogenation active component;

[0027] Feature 3: Lanthanum, cerium, cobalt and / or zinc (especially cerium) are used as promoter components;

[0028] Feature 4: The component loading process uses a step-by-step impregnation method to sequentially load the co-catalyst component and the hydrogenation active component onto the carrier.

[0029] In addition, when the hydrodeoxygenation catalyst satisfies the following four main characteristics at the same time and also satisfies other preferred characteristics described in the present application, the effect of the present invention can be further improved. Summary of the invention

[0030] The present invention includes the following solutions [1] to

[22] :

[0031] [1] A hydrodeoxygenation catalyst, wherein:

[0032] The catalyst comprises a phosphorus-modified alumina carrier and a hydrogenation active component and a promoter component supported on the phosphorus-modified alumina carrier.

[0033] The hydrogenation active component is only nickel,

[0034] The co-catalyst component is selected from at least one of lanthanum, cerium, cobalt and zinc,

[0035] The hydrodeoxygenation catalyst is manufactured by a manufacturing method comprising the following steps in sequence:

[0036] Step 1, preparing a phosphorus-modified alumina carrier;

[0037] Step 2, loading the co-catalyst component;

[0038] Step 3, loading the hydrogenation active component,

[0039] In steps 2 and 3, the co-catalyst component and the hydrogenation active component are loaded step by step by impregnation method respectively.

[0040] [2] The hydrodeoxygenation catalyst according to [1], wherein

[0041] The phosphorus-modified alumina carrier is a γ-Al2O3 carrier.

[0042] [3] The hydrodeoxygenation catalyst according to [1] or [2], wherein

[0043] Phosphorus is added to the raw material of the alumina carrier before the alumina carrier is formed.

[0044] In the phosphorus-modified alumina carrier, phosphorus exists in the form of phosphorus pentoxide, and the content of phosphorus pentoxide is 0.5 to 5% by mass, with the mass of alumina in the phosphorus-modified alumina carrier being 100% by mass.

[0045] [4] The hydrodeoxygenation catalyst according to [1] or [2], wherein

[0046] Phosphorus is added to the raw material of the alumina carrier before the alumina carrier is formed.

[0047] In the phosphorus-modified alumina carrier, phosphorus exists in the form of phosphorus pentoxide, and the content of phosphorus pentoxide is 1 to 3% by mass, with the mass of alumina in the phosphorus-modified alumina carrier being 100% by mass.

[0048] [5] The hydrodeoxygenation catalyst according to any one of [1] to [4], wherein

[0049] Taking the mass of the catalyst as 100 mass %, the content of nickel element in terms of oxide is:

[0050] The content of nickel oxide is 12 to 18% by mass.

[0051] [6] The hydrodeoxygenation catalyst according to any one of [1] to [5], wherein

[0052] Taking the mass of the catalyst as 100 mass %, the content of nickel element in terms of oxide is:

[0053] The content of nickel oxide is 12 to 16% by mass.

[0054] [7] The hydrodeoxygenation catalyst according to any one of [1] to [6], wherein

[0055] Taking the mass of the catalyst as 100 mass%, the content of lanthanum, cerium, cobalt and / or zinc elements in terms of oxides is:

[0056] The content of lanthanum oxide and / or cerium oxide and / or cobalt oxide and / or zinc oxide is 1 to 11% by mass.

[0057] [8] The hydrodeoxygenation catalyst according to any one of [1] to [7], wherein

[0058] Taking the mass of the catalyst as 100 mass %, the content of cerium element in terms of oxide is:

[0059] The content of cerium oxide is 6 to 10% by mass.

[0060] [9] The hydrodeoxygenation catalyst according to any one of [1] to [8], wherein

[0061] The co-catalyst component is only cerium.

[0062]

[10] The hydrodeoxygenation catalyst according to any one of [7] to [9], wherein

[0063] The rest was phosphorus-modified alumina support.

[0064]

[11] The hydrodeoxygenation catalyst according to any one of [1] to

[10] , wherein

[0065] The catalyst contains no molybdenum.

[0066]

[12] The hydrodeoxygenation catalyst according to any one of [1] to

[11] , wherein

[0067] The catalyst is free of added silicon, titanium, tungsten, fluorine and boron.

[0068]

[13] The hydrodeoxygenation catalyst according to any one of [1] to

[12] , wherein

[0069] The hydrogenation active component is loaded on the phosphorus-modified alumina carrier by using a complexing agent.

[0070]

[14] The hydrodeoxygenation catalyst according to

[13] , wherein

[0071] The complexing agent is citric acid and / or oxalic acid,

[0072] The mass ratio of the complexing agent to nickel oxide is 0.5:1 to 1:1.

[0073]

[15] A method for producing a hydrodeoxygenation catalyst, the method being a method for producing the hydrodeoxygenation catalyst according to any one of [1] to

[14] , wherein:

[0074] The manufacturing method comprises the following steps:

[0075] Step 1, obtaining a phosphorus-modified alumina support, wherein the phosphorus is added by adding a phosphorus-containing precursor to a raw material of the alumina support before the alumina support is formed;

[0076] Step 2, impregnating the phosphorus-modified alumina carrier obtained in step 1 with a solution containing a promoter component (preferably equal volume impregnation), drying and calcining the impregnated catalyst to obtain a primary impregnated catalyst;

[0077] Step 3, impregnating the once impregnated catalyst obtained in step 2 with an aqueous solution of a soluble nickel salt (preferably equal volume impregnation), drying and calcining the impregnated catalyst to obtain the hydrodeoxygenation catalyst.

[0078]

[16] The method for producing a hydrodeoxygenation catalyst according to

[15] , wherein

[0079] In step 1, 1 to 5% by weight of an extrusion aid sesbania powder is added to the pseudo-boehmite powder of the precursor of γ-Al2O3 and stirred evenly, and an aqueous solution containing 2 to 5% by weight of nitric acid, 1 to 5% by weight of citric acid and a precursor of phosphorus is added at a water-powder ratio of 0.6 to 1, and after kneading, the mixture is extruded into strips on an extruder, dried at 60 to 120°C, and calcined at 400 to 750°C for 3 to 6 hours to obtain a phosphorus-modified γ-Al2O3 carrier, wherein the concentration of nitric acid is 65 to 68%;

[0080] In step 2, the phosphorus-modified γ-Al2O3 carrier obtained in step 1 is first impregnated with an aqueous solution of a metal salt of a promoter component by an equal volume impregnation method, then dried at 100-140° C. for 8-12 hours, and then calcined at 350-550° C. for 3-6 hours to obtain a primary impregnation catalyst;

[0081] In step 3, the catalyst obtained by the single impregnation in step 2 is impregnated with an aqueous solution containing a soluble nickel salt and a complexing agent by an equal volume impregnation method, then dried at 100-140° C. for 8-12 hours, and then calcined at 350-550° C. for 3-6 hours to obtain the hydrodeoxygenation catalyst.

[0082]

[17] A hydrodeoxygenation reaction, wherein the reaction uses the catalyst described in any one of [1] to

[14] , wherein the catalyst is used after being reduced in a reactor, and the reaction is carried out at a reaction temperature of 170°C to 350°C.

[0083]

[18] The hydrodeoxygenation reaction as described in

[17] , wherein the reaction temperature is 190°C to 240°C.

[0084]

[19] The hydrodeoxygenation reaction as described in

[17] , wherein the reaction temperature is 200°C to 230°C.

[0085]

[20] The hydrodeoxygenation reaction as described in

[17] , wherein the reaction is carried out at a pressure of 2 to 6 MPa, a hydrogen-to-oil ratio of 200 to 800, and a liquid volume space velocity of 0.5 to 4 h -1 under the conditions of.

[0086]

[21] The hydrodeoxygenation reaction as described in

[17] , wherein the oxygenate removal rate of the reaction is greater than 99%.

[0087]

[22] The hydrodeoxygenation reaction as described in

[17] , wherein the alcohol removal rate of the reaction is 99% or more.

[0088]

[23] The hydrodeoxygenation reaction as described in

[17] , wherein the alcohol removal rate of the reaction is 100%.

[0089]

[24] Use of the hydrodeoxygenation catalyst according to any one of [1] to

[14] in the hydrodeoxygenation reaction of Fischer-Tropsch oil, wherein:

[0090] The reaction is carried out at a reaction temperature of 200°C to 230°C.

[0091]

[25] Use of the hydrodeoxygenation catalyst according to any one of [1] to

[14] in the hydrodeoxygenation reaction of an alcohol in a hydrocarbon containing an alcohol, wherein

[0092] The reaction is carried out at a reaction temperature of 200°C to 230°C.

[0093] Effects of the Invention

[0094] The present invention has the following advantages:

[0095] First, the hydrodeoxygenation catalyst of the present invention (hereinafter, sometimes referred to as "the catalyst of the present invention") can fully remove oxygen-containing compounds, especially alcohols, from Fischer-Tropsch synthesis oil at low temperatures. The hydrodeoxygenation catalyst of the present invention can also substantially completely or even completely remove alcohols from hydrocarbons containing alcohols at low temperatures.

[0096] Second, although the catalyst of the present invention, which uses nickel as the hydrogenation active component and cerium as the co-catalyst component, uses fewer types of metal elements, it can more fully remove oxygen-containing compounds, especially alcohols, from Fischer-Tropsch synthetic oil at low temperatures, and can also basically completely or even completely remove alcohols from hydrocarbons containing alcohols at even lower temperatures.

[0097] Third, the catalyst manufacturing steps of the present invention are fewer and the manufacturing process is simple.

[0098] Herein, unless otherwise stated, low temperature refers to a reaction temperature of 190°C to 240°C, and particularly refers to a reaction temperature of 200°C to 230°C. DETAILED DESCRIPTION

[0099] In the present specification, a numerical range represented by "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0100] <Hydrodeoxygenation Catalyst>

[0101] In Fischer-Tropsch synthetic oil, oxygen-containing compounds generally account for 5% to 15% by mass, and the rest are hydrocarbons.

[0102] The oxygen-containing compounds contained in the Fischer-Tropsch synthetic oil are generally alcohols, acids, aldehydes, esters and ketones. Among them, the alcohol is a normal alcohol, including methanol, ethanol, n-propanol, isobutanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, n-undecyl alcohol, n-dodecanol, n-tridecanol, n-tetradecyl alcohol, n-pentadecanol, n-hexadecanol, n-heptadecanol, n-octadecanol and n-nonadecanol.

[0103] The hydrodeoxygenation catalyst of the present invention satisfies the following four main characteristics simultaneously, so that the low-temperature hydrodeoxygenation reaction using the hydrodeoxygenation catalyst of the present invention can fully remove oxygen-containing compounds, especially alcohols, from the Fischer-Tropsch synthetic oil.

[0104] Feature 1: Using phosphorus-modified alumina carrier;

[0105] Feature 2: Nickel is used as the hydrogenation active component;

[0106] Feature 3: Lanthanum, cerium, cobalt and / or zinc (especially cerium) are used as promoter components;

[0107] Feature 4: The component loading process uses a step-by-step impregnation method to sequentially load the co-catalyst component and the hydrogenation active component onto the carrier.

[0108] The reason for achieving this effect is still under study, but the inventors believe that this effect is achieved by the above four characteristics being interrelated and synergistic. Even if one of the characteristics is not met but the other three characteristics are met, it is impossible to achieve a sufficiently high deoxidation rate at low temperatures.

[0109] The “removal rate of oxygen-containing compounds (deoxygenation rate)” is determined by gas chromatography and / or oxygen element analysis. For specific determination methods, please refer to the relevant description in the Examples section.

[0110] <Phosphorus-modified alumina support>

[0111] The catalyst of the present invention adopts a phosphorus-modified alumina carrier. The alumina carrier is preferably a γ-Al2O3 carrier. In the phosphorus-modified alumina carrier, phosphorus exists in the form of phosphorus pentoxide, and the mass of the alumina carrier (preferably the γ-Al2O3 carrier) in the phosphorus-modified alumina carrier is 100 mass%, and the content of phosphorus pentoxide is 0.5 to 5 mass%, preferably 1 to 3 mass%.

[0112] The phosphorus is added to the alumina support by adding a phosphorus-containing precursor to the raw material of the alumina support before the alumina support is formed.

[0113] The phosphorus-modified alumina carrier of the present invention is obtained by adding a phosphorus-containing precursor, an auxiliary agent and an acid to the raw material for preparing the alumina carrier before the alumina carrier is formed, and then forming, drying and calcining. Compared with the method of first forming the alumina carrier and then phosphorus-modifying the formed alumina carrier, the phosphorus modification method of the present invention not only reduces the preparation steps of the modified carrier but also helps to improve the deoxidation rate at low temperatures.

[0114] A complexing agent is preferably added during the manufacturing process of the phosphorus-modified alumina carrier. The complexing agent has a pore-expanding effect on the carrier, which helps to load the hydrogenation active component and the co-catalyst component, thereby helping to improve the deoxidation rate. The complexing agent is preferably citric acid and / or oxalic acid.

[0115] The inventors have found that, under the same feed amount, the higher the calcination temperature, the smaller the specific surface area and the larger the pore size. For the preparation of catalysts by impregnation method, the water absorption rate of the carrier is also a key parameter. Feed amount and calcination temperature also affect the water absorption rate of the carrier.

[0116] After studying the conditions for preparing the carrier, the inventors found that as long as the feeding amount of the phosphorus precursor is such that the content of phosphorus pentoxide in the phosphorus-modified alumina carrier reaches the content mentioned above, and the following substances, feeding amount ranges, proportions, drying and calcination temperatures, and calcination times are used, the obtained phosphorus-modified γ-Al2O3 carrier can be used to prepare the catalyst of the present invention, and the prepared catalyst of the present invention can achieve the target effect of the present invention.

[0117] Specifically, 1 to 5% by weight of an extrusion aid, sesbania powder, is added to the pseudo-boehmite powder, a precursor of γ-Al2O3, and the mixture is stirred evenly. Then, an aqueous solution containing 2 to 5% by weight of nitric acid (concentration 65 to 68%), 1 to 5% by weight of citric acid and a phosphorus precursor is added at a water-powder ratio of 0.6 to 1. After kneading, the mixture is extruded into strips on an extruder, dried at 60 to 120°C, and calcined at 400 to 750°C for 3 to 6 hours to obtain a phosphorus-modified γ-Al2O3 carrier (i.e., a phosphorus-modified alumina carrier).

[0118] It should be noted that if the calcination temperature exceeds 750° C., it is not conducive to improving the catalytic activity of the final catalyst.

[0119] The phosphorus precursor may be a soluble phosphate such as phosphoric acid, ammonium dihydrogen phosphate, diammonium phosphate, etc., preferably phosphoric acid.

[0120] In addition, the phosphorus-modified alumina carrier of the present invention is not modified with silicon-containing compounds and / or titanium-containing compounds, but is phosphorus-modified by simply adding a phosphorus-containing precursor to the raw materials for preparing the alumina carrier before the alumina carrier is formed. Therefore, the preparation process of the phosphorus-modified alumina carrier of the present invention is simpler.

[0121] <Hydrogenation active component>

[0122] The hydrogenation active component (also referred to as "primary catalytic active component") of the present invention is nickel. Nickel is fed in the form of an aqueous solution of a soluble nickel salt. The soluble nickel salt may be nickel nitrate, nickel acetate, nickel carbonate and / or basic nickel carbonate, preferably nickel nitrate.

[0123] <Co-catalyst component>

[0124] The co-catalyst component (also called "catalytic promoter") is usually inactive or has very low activity itself, but can significantly improve the activity of the catalyst when combined with the hydrogenation active component.

[0125] The co-catalyst component of the present invention is lanthanum, cerium, cobalt and / or zinc, preferably cerium. The inventors have found that in the catalyst of the present invention, compared with lanthanum, cobalt and zinc, the combination of the co-catalyst component cerium and the hydrogenation active component nickel has better catalytic activity and can achieve the same or higher deoxidation rate at a lower temperature.

[0126] The promoter component of the present invention is fed in the form of sulfate, chloride and / or nitrate, preferably nitrate.

[0127] The present invention preferably does not add molybdenum as a promoter component. The reasons are as follows:

[0128] Although in Example 1 of Patent Document 1, the molybdenum content accounts for the highest proportion among all metal elements (molybdenum oxide accounts for 18% by mass, and nickel and tungsten oxides account for 8% in total.), the inventors have found that the molybdenum element only plays a co-catalytic effect in the hydrodeoxygenation catalyst, that is, it only plays the role of an adjuvant. In addition, during the research process, the inventors found that for metal reduced hydrogenation catalysts, molybdenum as a co-catalyst component not only does not help to improve the hydrodeoxygenation activity of the catalyst, but also exceeds a certain content and reduces the hydrodeoxygenation activity of the catalyst. From this perspective, the catalyst of the present invention preferably does not contain molybdenum.

[0129] By the way, the present inventors have found that in Example 1 of Patent Document 1, the proportion of molybdenum oxide is too high and the proportion of nickel oxide is too low, and a sufficiently high deoxidation rate cannot be achieved at low temperatures. In Example 2 of Patent Document 1, although the proportion of molybdenum oxide is reduced and the proportion of nickel oxide is increased, a sufficiently high deoxidation rate cannot be achieved at low temperatures.

[0130] In the present invention, it is preferred not to actively or intentionally add tungsten, silicon, titanium, fluorine and boron to the catalyst (not excluding the case where they are mixed as impurities with a content of 0.1% by mass or less). This is because the inventors believe that the catalytic effect of these elements on the improvement of the deoxidation rate at low temperatures is lower than that of lanthanum, cerium, cobalt and zinc, especially cerium. As long as lanthanum, cerium, cobalt and / or zinc (especially cerium) are added, sufficient deoxidation can be achieved, and there is no need to add tungsten, silicon, titanium, fluorine and boron.

[0131] <Method for producing catalyst>

[0132] The method for preparing the hydrodeoxygenation catalyst of the present invention comprises the following steps in sequence:

[0133] Step 1, preparing a phosphorus-modified alumina carrier;

[0134] Step 2, loading the co-catalyst component;

[0135] Step 3, loading the hydrogenation active component,

[0136] In steps 2 and 3, the co-catalyst component and the hydrogenation active component are loaded step by step by impregnation method (ie, stepwise impregnation), preferably by equal volume impregnation.

[0137] Preferably, the hydrogenation active component is loaded on the alumina carrier using a complexing agent, wherein the mass ratio of the complexing agent to the nickel oxide is 0.5:1 to 1:1.

[0138] Specifically, the method for preparing the hydrodeoxygenation catalyst of the present invention comprises the following steps in sequence:

[0139] Step 1, obtaining a phosphorus-modified alumina carrier, wherein the phosphorus is added to the carrier by adding a phosphorus-containing precursor to the raw materials for preparing the alumina carrier before the alumina carrier is formed;

[0140] Step 2, impregnating the phosphorus-modified alumina carrier obtained in step 1 with a solution containing a promoter component in equal volume, drying and calcining the impregnated catalyst to obtain a primary impregnated catalyst;

[0141] Step 3, impregnating the once impregnated catalyst obtained in step 2 with an aqueous solution of a soluble nickel salt in equal volume, drying and calcining the impregnated catalyst to obtain the hydrodeoxygenation catalyst.

[0142] More specifically:

[0143] In step 1, 1 to 5% by mass of an extrusion aid sesbania powder is added to the pseudo-boehmite powder of the precursor of γ-Al2O3 and stirred evenly, and an aqueous solution containing 2 to 5% by mass of nitric acid (concentration 65 to 68%), 1 to 5% by mass of citric acid and a phosphorus precursor is added at a water-powder ratio of 0.6 to 1, and after kneading, the mixture is extruded into strips on an extruder, dried at 60 to 120°C, and calcined at 400 to 750°C for 3 to 6 hours to obtain a phosphorus-modified γ-Al2O3 carrier;

[0144] In step 2, the phosphorus-modified γ-Al2O3 carrier obtained in step 1 is first impregnated with an aqueous solution of a metal salt of the promoter component by an equal volume impregnation method, then dried at 100-140°C for 8-12 hours, and then calcined at 350-550°C for 3-6 hours to obtain a single impregnation catalyst.

[0145] In step 3, the catalyst obtained by the single impregnation in step 2 is impregnated with an aqueous solution containing a soluble nickel salt and a complexing agent by an equal volume impregnation method, then dried at 100-140° C. for 8-12 hours, and then calcined at 350-550° C. for 3-6 hours to obtain the hydrodeoxygenation catalyst.

[0146] The complexing agent in step 3 is preferably citric acid and / or oxalic acid.

[0147] <Hydrodeoxygenation reaction>

[0148] The catalyst of the present invention can effectively catalyze the low-temperature hydrodeoxygenation reaction of oxygen-containing compounds in Fischer-Tropsch synthetic oil, especially can effectively catalyze the low-temperature removal of alcohols in Fischer-Tropsch synthetic oil. In addition, the catalyst of the present invention can effectively catalyze the low-temperature hydrodeoxygenation reaction of alcohols in hydrocarbons containing alcohols.

[0149] The hydrocarbons are white spirit and / or pure hydrocarbons, and the alcohols are normal alcohols.

[0150] The reactor for the hydrodeoxygenation reaction adopts a fixed bed reactor.

[0151] The hydrodeoxygenation reaction is carried out using the catalyst of the present invention. The catalyst is first reduced in a reactor under a hydrogen atmosphere and then used.

[0152] The hydrodeoxygenation reaction can be carried out at a reaction temperature of 170 to 350°C. However, from the purpose of the present invention, the reaction temperature is preferably low temperature (190 to 240°C, preferably 200 to 230°C). Because the catalyst of the present invention is used, the hydrodeoxygenation reaction can be carried out at low temperature. Moreover, even if it is carried out at low temperature, the deoxygenation rate is not lower than or even higher than the hydrodeoxygenation reaction carried out at a higher temperature using an existing catalyst. Hereinafter, the hydrodeoxygenation reaction carried out at low temperature is sometimes referred to as "low-temperature hydrodeoxygenation reaction".

[0153] In addition, for the simulated oil (hydrocarbons containing alcohols) described in the examples, substantially complete or even complete deoxygenation can be achieved at a relatively low reaction temperature (e.g., below 210°C). For real raw materials of Fischer-Tropsch synthetic oil, extremely high deoxygenation rates can also be achieved at slightly higher reaction temperatures (e.g., around 230°C). This is because there are many types of oxygen-containing compounds and a wide carbon number distribution in the real raw materials of Fischer-Tropsch synthetic oil, so the reaction temperature needs to be slightly increased to achieve more complete deoxygenation. However, relative to the prior art, a reaction temperature below 240°C (e.g., around 230°C) is still a low temperature.

[0154] The reaction pressure of the low-temperature hydrodeoxygenation reaction using the catalyst of the present invention is 2-6 MPa, the hydrogen-to-oil ratio is 200-800, and the liquid volume space velocity is 0.5-4 h -1 .

[0155] The "low-temperature hydrodeoxygenation reaction" can fully remove oxygen-containing compounds at low temperatures by using the catalyst of the present invention. The deoxygenation rate of oxygen-containing compounds is 99% or more, among which the alcohol removal rate is 99% or more, preferably 100%.

[0156] Through the low-temperature hydrodeoxygenation reaction using the catalyst of the present invention, the oxygen-containing compounds contained in the Fischer-Tropsch synthesis oil can be fully removed, especially the alcohols contained in the Fischer-Tropsch synthesis oil can be substantially completely or completely removed. In addition, through the low-temperature hydrodeoxygenation reaction using the catalyst of the present invention, the alcohols in the hydrocarbons containing alcohols can be substantially completely or completely removed.

[0157] <Application and Use>

[0158] Suitable applications of the catalyst of the present invention are low-temperature hydrodeoxygenation refining of Fischer-Tropsch synthetic oil and low-temperature removal of alcohol from hydrocarbons containing alcohol.

[0159] Example

[0160] Source of raw materials: including raw material name, specifications, manufacturers, etc. see Table 1.

[0161] Table 1 Experimental raw materials

[0162]

[0163] <Evaluation and analysis method of oxygen removal rate>

[0164] The reaction raw materials for evaluation are simulated oil or low-temperature Fischer-Tropsch synthesis oil (i.e., Fischer-Tropsch synthesis oil produced by low-temperature process). The simulated oil is an n-heptane solution containing the model compound raw material n-butanol as an oxygen-containing compound, wherein the content of n-butanol is 15% by mass. The properties of low-temperature Fischer-Tropsch synthesis oil and the composition of oxygen-containing compounds therein are shown in Tables 2 and 3.

[0165] The total oxygen mass content in the low-temperature Fischer-Tropsch synthetic oil raw material and the deoxygenated product can be analyzed by PEEA2400 oxygen element analyzer. This analysis method can determine the mass of oxygen in all oxygen-containing organic compounds such as alcohols, acids, aldehydes, ketones, esters, etc. in the oil. The olefin content is analyzed by bromine value bromine index instrument. The distillation range distribution is determined by gas chromatography simulated distillation method. The chromatographic model is Agilent7890B, equipped with hydrogen flame ionization detector (FID) and metal capillary column (DBHT-SIMD).

[0166] Gas chromatography was used to determine the composition of normal alcohols in simulated oil and low-temperature Fischer-Tropsch synthetic oil, and the deoxygenation rate was calculated. Specifically, the reaction (liquid phase) product analysis included group composition and oxygenated compound analysis, and the analysis was performed using an Agilent 7890B gas chromatograph equipped with an HP-PONA (50m×0.2mm×0.5μm) capillary column and a hydrogen flame detector (FID).

[0167] Table 2 Properties of low temperature Fischer-Tropsch synthetic oil used for evaluation of catalyst performance for hydrodeoxygenation

[0168]

[0169]

[0170] Note: The total oxygen mass fraction is determined by an oxygen element analyzer.

[0171] Table 3 Composition of normal alcohols in low temperature Fischer-Tropsch synthetic oil

[0172] Name of alcohol Mass fraction / % Methanol 0.019 Ethanol 0.097 n-Propanol 0.154 Isobutanol 0.009 n-Butanol 0.522 n-Amyl alcohol 0.946 n-Hexanol 1.363 n-Heptanol 1.361 n-Octanol 1.389 n-nonanol 1.242 n-Decanol 1.142 n-Undecyl alcohol 0.841 n-Dodecanol 0.679 n-Tridecyl alcohol 0.562 n-Tetradecyl Alcohol 0.362 n-Pentadecanol 0.299 Hexadecanol 0.238 n-Heptadecanol 0.094 n-Octadecanol 0.061 n-Nonadecanol 0.025 total 11.405

[0173] <Implementation of Catalyst Performance Evaluation Experiment>

[0174] Catalyst performance evaluation experiments were carried out on a 10mL four-channel fixed-bed oil hydrogenation evaluation device (fixed-bed reactor).

[0175] The catalyst was crushed and sieved to 20-40 mesh, and 10 mL was taken and loaded into the fixed bed reactor. Before the evaluation reaction raw materials were fed, the catalyst was reduced at 420°C for 6 hours under H2 atmosphere, and then cooled to the reaction temperature of each example recorded in Tables 4 to 6, and then the evaluation reaction raw materials were fed. After the feed was stable, a liquid sample was taken for analysis.

[0176] The reaction raw materials for evaluation were respectively the reaction raw materials of the embodiments, comparative examples and reference examples recorded in Tables 4 to 6 (except for Example 7 which used low-temperature Fischer-Tropsch synthetic oil, the other examples used simulated oil); the reaction temperatures were respectively the reaction temperatures of the embodiments, comparative examples and reference examples recorded in Tables 4 to 6; the reaction pressure was 4 MPa, and the liquid volume space velocity was 1 h -1, the hydrogen / oil volume ratio is 400.

[0177] Carrier Preparation Example 1

[0178] Weigh 300.00g (225.00g on dry basis) of pseudo-boehmite powder and 8.00g of sesbania powder, add deionized water at a water-powder ratio of 0.7:1, add 11.00g of nitric acid (concentration content 65-68%), 6.00g of citric acid and 3.66g of phosphoric acid (content 85%) to the deionized water. After kneading, use a 1.50mm orifice plate to extrude strips on an extruder, dry at 110°C, and calcine at 550°C for 4h to obtain a phosphorus-modified γ-Al2O3 carrier.

[0179] Carrier Preparation Example 2

[0180] A phosphorus-modified γ-Al2O3 carrier was prepared in the same manner as in Carrier Preparation Example 1, except that the amount of phosphoric acid added was changed to 5.48 g.

[0181] Carrier Preparation Example 3

[0182] A phosphorus-modified γ-Al2O3 carrier was prepared in the same manner as in Carrier Preparation Example 1, except that the amount of phosphoric acid added was changed to 7.31 g.

[0183] Carrier Preparation Example 4

[0184] Except for changing the amount of phosphoric acid fed to 10.96 g, the rest was carried out in the same manner as in Carrier Preparation Example 1 to obtain a phosphorus-modified γ-Al2O3 carrier.

[0185] Carrier Preparation Example 5

[0186] A phosphorus-modified γ-Al2O3 carrier was prepared in the same manner as in Carrier Preparation Example 1, except that the amount of phosphoric acid added was changed to 5.48 g.

[0187] Carrier Preparation Example 6

[0188] A phosphorus-modified γ-Al2O3 carrier was prepared in the same manner as in Carrier Preparation Example 1, except that the amount of phosphoric acid added was changed to 7.31 g.

[0189] Carrier Preparation Example 7

[0190] Weigh 300.00g (225.00g on dry basis) of pseudo-boehmite powder and 10.00g of sesbania powder, add deionized water at a water-powder ratio of 0.7:1, add 6.00g of nitric acid (concentration content 65-68%), 7.50g of citric acid and 7.31g of phosphoric acid (content 85%) to the deionized water, after kneading, select a 1.50mm orifice plate to extrude strips on an extruder, dry at 110°C, and calcine at 750°C for 4h to obtain a phosphorus-modified γ-Al2O3 carrier.

[0191] Carrier Preparation Example 8

[0192] Weigh 300.00g (225.00g on dry basis) of pseudo-boehmite powder and 15.00g of sesbania powder, add deionized water at a water-powder ratio of 0.8:1, add 7.00g of nitric acid (concentration content 65-68%), 7.50g of citric acid and 7.31g of phosphoric acid (content 85%) to the deionized water, after kneading, select a 1.50mm orifice plate to extrude strips on an extruder, dry at 110°C, and calcine at 550°C for 4h to obtain a phosphorus-modified γ-Al2O3 carrier.

[0193] Carrier Preparation Example 9

[0194] Weigh 300.00g (225.00g on dry basis) of pseudo-boehmite powder and 12.00g of sesbania powder, add deionized water at a water-powder ratio of 0.8:1, add 7.00g of nitric acid (concentration content 65-68%), 14.0g of citric acid and 7.31g of phosphoric acid (content 85%) to the deionized water, after kneading, select a 1.50mm orifice plate to extrude strips on an extruder, dry at 110°C, and calcine at 550°C for 4h to obtain a phosphorus-modified γ-Al2O3 carrier.

[0195] Carrier Preparation Comparative Example

[0196] Except for changing the amount of phosphoric acid fed to 0 g (i.e., no phosphoric acid was fed), the rest of the process was carried out in the same manner as in Carrier Preparation Example 1 to obtain a γ-Al2O3 carrier.

[0197] Example 1

[0198] According to Carrier Preparation Example 1, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0199] Weigh 30.00g of the modified alumina carrier, prepare 10.53g of cobalt nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 120℃ for 8h, and the dried catalyst is placed in a muffle furnace and calcined at 450℃ for 4h. A single impregnation catalyst is obtained.

[0200] By using the equal volume impregnation method, 8.58g of nickel carbonate and 4.32g of citric acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 120°C for 8 hours, and the dried catalyst was placed in a muffle furnace and calcined at 450°C for 4 hours to obtain a hydrodeoxygenation catalyst.

[0201] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0202] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0203] Example 2

[0204] According to carrier preparation example 2, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0205] Weigh 30.00g of the modified alumina carrier, prepare 4.79g of lanthanum nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 100℃ for 12h, and the dried catalyst is placed in a muffle furnace and calcined at 500℃ for 3h. A primary impregnation catalyst is obtained.

[0206] By using the equal volume impregnation method, 21.02g of nickel nitrate and 4.32g of oxalic acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 100°C for 12 hours, and the dried catalyst was placed in a muffle furnace and calcined at 500°C for 3 hours to obtain a hydrodeoxygenation catalyst.

[0207] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0208] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0209] Example 3

[0210] According to carrier preparation example 3, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0211] Weigh 30.00g of the modified alumina carrier, prepare 7.57g of cerium nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 110℃ for 10h, and the dried catalyst is placed in a muffle furnace and calcined at 450℃ for 4h to obtain a primary impregnation catalyst.

[0212] By using the equal volume impregnation method, 18.69g of nickel nitrate and 3.36g of citric acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 110°C for 10 hours, and the dried catalyst was placed in a muffle furnace and calcined at 450°C for 4 hours to obtain a hydrodeoxygenation catalyst.

[0213] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0214] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0215] Comparative Example 1

[0216] Weigh 30.00 g of the phosphorus-modified alumina carrier prepared in Example 3, adopt the component loading process of co-impregnation, and prepare 18.69 g of nickel nitrate, 3.36 g of citric acid, and 7.57 g of cerium nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6 hours. The impregnated catalyst is dried at 110°C for 10 hours, and the dried catalyst is placed in a muffle furnace and calcined at 450°C for 4 hours. A hydrodeoxygenation catalyst is obtained.

[0217] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0218] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0219] Example 4

[0220] According to carrier preparation example 4, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0221] Weigh 30.00g of the modified alumina carrier, prepare 6.32g of cobalt nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 130℃ for 6h, and the dried catalyst is placed in a muffle furnace and calcined at 400℃ for 4h. A single impregnation catalyst is obtained.

[0222] By using the equal volume impregnation method, 23.36g of nickel nitrate, 3.00g of citric acid, and 3.00g of oxalic acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 130°C for 6 hours, and the dried catalyst was placed in a muffle furnace and calcined at 400°C for 4 hours to obtain a hydrodeoxygenation catalyst.

[0223] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0224] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0225] Example 5

[0226] According to carrier preparation example 5, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0227] Weigh 30.00g of modified alumina carrier, and prepare 6.81g of cerium nitrate and 2.19g of zinc nitrate into a certain concentration of aqueous solution according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 120℃ for 8h, and the dried catalyst is placed in a muffle furnace and calcined at 450℃ for 5h. A single impregnation catalyst is obtained.

[0228] By using the equal volume impregnation method, 21.02g of nickel nitrate and 3.24g of citric acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 120°C for 8 hours, and the dried catalyst was placed in a muffle furnace and calcined at 450°C for 5 hours to obtain a hydrodeoxygenation catalyst.

[0229] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0230] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0231] Example 6

[0232] According to carrier preparation example 6, a phosphorus-modified γ-Al2O3 carrier was prepared.

[0233] Weigh 30.00g of modified alumina carrier, and prepare 2.39g of lanthanum nitrate and 6.32g of cobalt nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 120℃ for 8h, and the dried catalyst is placed in a muffle furnace and calcined at 450℃ for 5h. A single impregnation catalyst is obtained.

[0234] By using the equal volume impregnation method, 21.02g of nickel nitrate and 3.24g of citric acid were prepared into an aqueous solution of a certain concentration, which was slowly dripped onto the catalyst obtained by the first impregnation, stirred evenly, and impregnated for 6 hours. The impregnated catalyst was dried at 120°C for 8 hours, and the dried catalyst was placed in a muffle furnace and calcined at 450°C for 5 hours to obtain a hydrodeoxygenation catalyst.

[0235] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0236] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0237] Comparative Example 2

[0238] Weigh 30.00 g of the phosphorus-modified alumina carrier prepared in Example 6, adopt the co-impregnation component loading process, and prepare 21.02 g of nickel nitrate, 3.24 g of citric acid, 2.39 g of lanthanum nitrate, and 6.32 g of cobalt nitrate into an aqueous solution of a certain concentration according to the equal volume impregnation method, slowly drop it onto the alumina carrier, stir evenly, and impregnate for 6 hours. The impregnated catalyst is dried at 120°C for 8 hours, and the dried catalyst is placed in a muffle furnace and calcined at 450°C for 5 hours. A single impregnation catalyst is obtained.

[0239] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0240] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0241] Comparative Example 3

[0242] According to the carrier preparation comparative example, a γ-Al2O3 carrier was prepared.

[0243] Weigh 30.00g of the above alumina carrier, and prepare a certain concentration of aqueous solution with 18.69g of nickel nitrate and 3.36g of citric acid according to the equal volume impregnation method, slowly drop it onto the catalyst obtained by the first impregnation, stir evenly, and impregnate for 6h. The impregnated catalyst is dried at 110℃ for 10h, and the dried catalyst is placed in a muffle furnace and calcined at 450℃ for 4h to obtain a hydrodeoxygenation catalyst.

[0244] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0245] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0246] Comparative Example 4

[0247] The same method as Example 2 was followed except that citric acid was not added during the preparation of the phosphorus-modified alumina support.

[0248] The obtained catalyst performance evaluation was carried out according to the above section <Implementation of Catalyst Performance Evaluation Experiment>.

[0249] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0250] Example 7

[0251] Except for changing the reaction raw material for evaluation to low-temperature Fischer-Tropsch synthetic oil (the properties of the synthetic oil and the normal alcohol composition are shown in Tables 2 and 3) and changing the reaction temperature to 230°C, the rest is carried out in the same manner as Example 3 (i.e., using the catalyst of Example 3 and changing the catalyst performance evaluation experimental conditions).

[0252] The catalyst composition and catalyst performance evaluation results are shown in Table 4.

[0253] Example 8

[0254] The same procedure as in Example 7 was followed except that the deoxidation rate was changed to a value calculated using the total oxygen mass fraction measured by an oxygen element analyzer.

[0255] The catalyst composition and catalyst performance evaluation results are shown in Table 5.

[0256]

[0257] Table 5

[0258]

[0259] Note: The total oxygen mass fraction is the result measured by oxygen element analyzer.

[0260] It can be seen from Table 4 that the embodiments using a phosphorus-modified alumina carrier, nickel as the hydrogenation active component, lanthanum, cerium, cobalt and / or zinc as the co-catalyst components and the component loading process using step-by-step impregnation (the embodiments satisfying the aforementioned characteristics 1 to 4 at the same time) can achieve a deoxygenation rate of more than 99% even at low temperatures, whether for simulated oil or for low-temperature Fischer-Tropsch synthetic oil feedstock, and can even achieve a deoxygenation rate of 100% (n-alcohol removal rate).

[0261] In particular, embodiments 3 and 7 use only two elements, nickel and cerium. For simulated oil, a deoxygenation rate of 100% can be achieved at a low temperature of 200-210°C. For low-temperature Fischer-Tropsch synthetic oil raw materials, a deoxygenation rate of more than 99% can be achieved at a low temperature of 230°C.

[0262] According to the oxygen element analyzer, the total oxygen mass fraction of the low-temperature Fischer-Tropsch synthetic oil raw material is 1.89% (see Table 2). As can be seen from Table 5, the experimental results of Example 8 measured by the oxygen element analyzer show that the oxygen content is extremely low, even as low as 0 (below the instrument detection limit). This shows that based on the results of the oxygen element analyzer, the oxygen-containing compounds in the low-temperature Fischer-Tropsch synthetic oil are fully removed.

[0263] From the above results, it can be seen that the catalyst of the present invention not only has a good removal effect on alcohol, but also has a good removal effect on other oxygen-containing compounds in synthetic oil, and can fully remove the oxygen-containing compounds contained in low-temperature Fischer-Tropsch synthetic oil at low temperature.

[0264] Comparative Examples 1-3 do not simultaneously meet the aforementioned characteristics 1-4, and the deoxidation rate level is significantly lower than that of Examples 1-6.

[0265] Comparative Example 4 is the same as Example 2 except that no complexing agent is added during the preparation of the phosphorus-modified alumina carrier. The deoxidation rate is lower than that of Example 2 and does not reach more than 99%.

[0266] It should be noted that, since trace amounts of oxygen-containing compounds can cause significant adverse effects on subsequent processes and equipment (for example, causing equipment corrosion, etc.), the 1% difference between the deoxidation rates of 98% and 99% is also a significant difference.

[0267] Furthermore, according to the research of the present inventors, existing catalysts cannot achieve the deoxygenation rate of the above-mentioned embodiment at low temperatures, whether for simulated oil or for low-temperature Fischer-Tropsch synthetic oil feedstock.

[0268] Reference Examples 1 to 3, Example 9

[0269] Except that the reaction temperature was adjusted to the temperature shown in Table 6, the other operations were carried out in the same manner as in Example 3.

[0270] The catalyst composition and catalyst performance evaluation results are shown in Table 6.

[0271] Table 6

[0272]

[0273] It can be seen from Table 6 that the catalyst of the present invention, especially the catalyst of the present invention satisfying the above-mentioned characteristics 1 to 4, can achieve a deoxidation rate of 100% for simulated oil at a low temperature of 200°C.

[0274] Reference Examples 4 and 5

[0275] The same procedure as in Example 3 was followed except that the cerium nitrate used as the co-catalyst was replaced by ammonium heptamolybdate, the amounts of nickel nitrate and ammonium heptamolybdate were adjusted to achieve the contents shown in Table 7, and the reaction temperature was adjusted to 210°C.

[0276] The catalyst composition and catalyst performance evaluation results are shown in Table 7.

[0277] Table 7

[0278]

[0279] As can be seen from Table 7, at low temperatures, the conventional catalysts with nickel as the hydrogenation active component and molybdenum as the co-catalyst component cannot achieve a sufficient deoxidation rate. Moreover, if the molybdenum content is increased, the deoxidation rate will be further reduced. In other words, the molybdenum element does not contribute to the improvement of the low-temperature deoxidation rate.

[0280] It should be noted that, according to the research of the present inventors, even if a carrier prepared by any one of carrier preparation examples 7 to 9 is used in the above-mentioned embodiments, the target effect of the present invention can be achieved in the same manner as in the embodiments.

[0281] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A hydrodeoxygenation catalyst, characterized in that The catalyst comprises a phosphorus-modified alumina carrier and a hydrogenation active component and a promoter component supported on the phosphorus-modified alumina carrier. The hydrogenation active component is only nickel, The co-catalyst component is selected from at least one of lanthanum, cerium, cobalt and zinc, The hydrodeoxygenation catalyst is manufactured by a manufacturing method comprising the following steps in sequence: Step 1, preparing a phosphorus-modified alumina carrier; Step 2, loading the co-catalyst component; Step 3, loading the hydrogenation active component, In steps 2 and 3, the co-catalyst component and the hydrogenation active component are loaded step by step by impregnation method respectively.

2. The hydrodeoxygenation catalyst according to claim 1, characterized in that The phosphorus-modified alumina carrier is a γ-Al2O3 carrier.

3. The hydrodeoxygenation catalyst according to claim 1, characterized in that Phosphorus is added to the raw material of the alumina carrier before the alumina carrier is formed. In the phosphorus-modified alumina carrier, phosphorus exists in the form of phosphorus pentoxide, and the content of phosphorus pentoxide is 0.5 to 5% by mass, with the mass of alumina in the phosphorus-modified alumina carrier being 100% by mass.

4. The hydrodeoxygenation catalyst according to claim 1, characterized in that Phosphorus is added to the raw material of the alumina carrier before the alumina carrier is formed. In the phosphorus-modified alumina carrier, phosphorus exists in the form of phosphorus pentoxide, and the content of phosphorus pentoxide is 1 to 3% by mass, with the mass of alumina in the phosphorus-modified alumina carrier being 100% by mass.

5. The hydrodeoxygenation catalyst according to claim 1, characterized in that Taking the mass of the catalyst as 100 mass %, the content of each metal element in terms of oxide is: The content of nickel oxide is 12 to 18% by mass. The content of lanthanum oxide and / or cerium oxide and / or cobalt oxide and / or zinc oxide is 1 to 11% by mass; The rest was phosphorus-modified alumina support.

6. The hydrodeoxygenation catalyst according to claim 1, characterized in that The co-catalyst component is only cerium.

7. The hydrodeoxygenation catalyst according to claim 6, characterized in that Taking the mass of the catalyst as 100 mass %, the content of each metal element in terms of oxide is as follows: The content of nickel oxide is 12 to 16% by mass. The content of cerium oxide is 6 to 10% by mass. The rest was phosphorus-modified alumina support.

8. The hydrodeoxygenation catalyst according to claim 1, characterized in that The catalyst contains no molybdenum.

9. The hydrodeoxygenation catalyst according to claim 1, characterized in that The catalyst is free of added silicon, titanium, tungsten, fluorine and boron.

10. The hydrodeoxygenation catalyst according to claim 1, characterized in that The hydrogenation active component is loaded on the phosphorus-modified alumina carrier by using a complexing agent.

11. The hydrodeoxygenation catalyst according to claim 10, characterized in that The complexing agent is citric acid and / or oxalic acid, The mass ratio of the complexing agent to nickel oxide is 0.5:1 to 1:

1.

12. A method for producing a hydrodeoxygenation catalyst, the method being a method for producing the hydrodeoxygenation catalyst according to any one of claims 1 to 11, characterized in that: The manufacturing method comprises the following steps: Step 1, obtaining a phosphorus-modified alumina support, wherein the phosphorus is added by adding a phosphorus-containing precursor to a raw material of the alumina support before the alumina support is formed; Step 2, impregnating the phosphorus-modified alumina carrier obtained in step 1 with a solution containing a promoter component, and drying and calcining the impregnated catalyst to obtain a primary impregnated catalyst; Step 3, impregnating the once impregnated catalyst obtained in step 2 with an aqueous solution of a soluble nickel salt, and drying and calcining the impregnated catalyst to obtain the hydrodeoxygenation catalyst.

13. The method for producing a hydrodeoxygenation catalyst according to claim 12, wherein: In step 1, 1 to 5% by weight of an extrusion aid sesbania powder is added to the pseudo-boehmite powder of the precursor of γ-Al2O3 and stirred evenly, and an aqueous solution containing 2 to 5% by weight of nitric acid, 1 to 5% by weight of citric acid and a precursor of phosphorus is added at a water-powder ratio of 0.6 to 1, and after kneading, the mixture is extruded on an extruder to form strips, dried at 60 to 120°C, and calcined at 400 to 750°C for 3 to 6 hours to obtain a phosphorus-modified γ-Al2O3 carrier, wherein the concentration of nitric acid is 65 to 68%; In step 2, the phosphorus-modified γ-Al2O3 carrier obtained in step 1 is first impregnated with an aqueous solution of a metal salt of a promoter component by an equal volume impregnation method, then dried at 100-140° C. for 8-12 hours, and then calcined at 350-550° C. for 3-6 hours to obtain a primary impregnation catalyst; In step 3, the catalyst obtained by the single impregnation in step 2 is impregnated with an aqueous solution containing a soluble nickel salt and a complexing agent by an equal volume impregnation method, then dried at 100-140° C. for 8-12 hours, and then calcined at 350-550° C. for 3-6 hours to obtain the hydrodeoxygenation catalyst.

14. A hydrodeoxygenation reaction, characterized in that: The reaction uses the catalyst according to any one of claims 1 to 11, wherein the catalyst is used after being reduced in a reactor, and the reaction is carried out at a reaction temperature of 170° C. to 350° C.

15. The hydrodeoxygenation reaction according to claim 14, characterized in that The reaction temperature is 190°C to 240°C.

16. The hydrodeoxygenation reaction according to claim 14, characterized in that The reaction temperature is 200°C to 230°C.

17. The hydrodeoxygenation reaction according to claim 14, characterized in that The reaction is carried out at a pressure of 2 to 6 MPa, a hydrogen-to-oil ratio of 200 to 800, and a liquid volume space velocity of 0.5 to 4 h -1 under the conditions of.

18. The hydrodeoxygenation reaction according to claim 14, characterized in that The oxygenate removal rate of the reaction is above 99%.

19. The hydrodeoxygenation reaction according to claim 14, characterized in that The alcohol removal rate of the reaction is above 99%.

20. The hydrodeoxygenation reaction according to claim 14, characterized in that The alcohol removal rate of the reaction was 100%.

21. Use of the hydrodeoxygenation catalyst according to any one of claims 1 to 11 in the hydrodeoxygenation reaction of Fischer-Tropsch synthetic oil, characterized in that: The reaction is carried out at a reaction temperature of 200°C to 230°C.

22. Use of the hydrodeoxygenation catalyst according to any one of claims 1 to 11 in the hydrodeoxygenation reaction of alcohols in hydrocarbons containing alcohols, characterized in that: The reaction is carried out at a reaction temperature of 200°C to 230°C.

Citation Information

Patent Citations

  • Catalyst for hydrogenation of Fischer-Tropsch synthesis oil, preparation method as well as application thereof

    CN101733119A

  • Catalyst for hydrogenation refining of Fischer-Tropsch synthetic oil, as well as preparation method and application thereof

    CN103191754A

  • Hydrodeoxygenation catalyst for Fischer Tropsch synthesis oil and preparation method and application of hydrodeoxygenation catalyst

    CN102794181A

  • Catalyst for preparing biodiesel through hydrogenation of castor oil and preparation method of catalyst

    CN103721741A

  • Low-temperature deoxidation catalyst for synthesis gas and preparation and application thereof

    CN110721707A

Cited By

  • Powder-loaded nickel catalyst and preparation method and application thereof

    CN122298436A